Variational Approach to Impulsive Differential Equations with Dirichlet Boundary Conditions. (24th November 2010) - Chen, Huiwen; Li, Jianli
Abstract : We study the existence ofn distinct pairs of nontrivial solutions for impulsive differential equations with Dirichlet boundary conditions by using variational methods and critical point theory.